Multifunctional Toxins in Snake Venoms and Therapeutic Implications: From Pain to Hemorrhage and Necrosis - Ferraz, Camila R.; Arrahman, Arif; Xie, Chunfang; Casewell, Nicholas R.; Lewis, Richard J.; Kool, Jeroen; Cardoso, Fernanda C. (Frontiers in Ecology and Evolution, 2019)
Animal venoms have evolved over millions of years for prey capture and defense from predators and rivals. Snake venoms, in particular, have evolved a wide diversity of peptides and proteins that induce harmful inflammatory and neurotoxic effects including severe pain and paralysis, hemotoxic effects, such as hemorrhage and coagulopathy, and cytotoxic/myotoxic effects, such as inflammation and necrosis. If untreated, many envenomings result in death or severe morbidity in humans and, despite advances in management, snakebite remains a major public health problem, particularly in developing countries. Consequently, the World Health Organization recently recognized snakebite as a neglected tropical disease that affects ~2.7 million p.a. The major protein classes found in snake venoms are phospholipases, metalloproteases, serine proteases and three-finger peptides. The mechanisms of action and pharmacological properties of many snake venom toxins have been elucidated, revealing a complex multifunctional cocktail that can act synergistically to rapidly immobilize prey and deter predators. However, despite these advances many snake toxins remain to be structurally and pharmacologically characterized. In this review, the multifunctional features of the peptides and proteins found in snake venoms, as well as their evolutionary histories, are discussed with the view to identifying novel modes of action and improving snakebite treatments.